Congenital Hepatopulmonary Fusion - Rocha, Gustavo M. D. (European Journal of Pediatric Surgery, 2022)
Congenital hepatopulmonary fusion (HPF) is a rare anomaly characterized by a fusion between the liver and lung parenchyma. HPF cases have been scarcely reported in the literature. An extensive search of publications was performed in the PubMed and Google Scholar databases without a time limit. In total, 34 clinical case reports were found in the literature, and a study by the Congenital Diaphragmatic Hernia (CDH) Study Group reported data on 10 patients with HPF. Of these 44 infants, 20 were male, 20 were female, and four were reported without gender specification. Nineteen (43.2%) patients required intubation on the first day of life. Six (13.6%) patients had their clinical presentation during the first year of life, and four (9%) clinically presented with HPF between 2.5 and 11 years of age. In these patients, cough, asthma-like symptoms, dyspnea, hemoptysis, right-side chest pain, respiratory infections, and pneumonia were the relevant clinical signs. Right-lung vascular anomalies were present in 18 (40.9%) patients. A complete liver and lung separation was successful in 17 (38.6%) patients. The overall survival was 56.8%. Congenital HPF has no gender predominance. In most cases, it behaves similar to a right CDH in need of resuscitation and intubation after birth. The majority of the cases are discovered during the surgical procedure for CDH. The best surgical approach has not been established and depends on the degree of fusion and vascular anomalies. An advanced imaging assessment is necessary before a surgical approach is attempted. The prognosis is ominous.
Keywords: case series; congenital diaphragmatic hernia; hepatopulmonary fusion; liver; lungs; diaphragm; neonate